THE ROLE OF PARENTAL INVOLVEMENT TOWARDS THE STUDENTS’ LEARNING MOTIVATION - Hendita Rifki Alfiansyah (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2019)
Abstract:This research aimed to identify the role of parental involvement toward the students’ learning motivation. This research was conducted using quantitative method. The approach of this research was ex-post facto. The subjects of the research were 136 fourth grade students of elementary school. The instrument of the research used was questionnaire. The technique of data analysis was regression analysis. The result of the research showed that the parental involvement role on learning motivation reaches 39.7%. It could be concluded that the parental involvement role has positive effect on the fourth grade students’ learning motivation. This research showed the importance of parental involvement role towards students’ learning motivation. These results were expected to provide understanding from the school committee to assure parents that their supports were important in the process of their children education. Therefore, all parties should be involved in improving the quality of children's education.Abstrak:Penelitian ini bertujuan untuk mengkaji peranan orng tua terhadap motivasi belajar siswa. Penelitian ini menggunakan metode kuantitatif dengan pendekatan ex-post facto. Subjek pada penelitian ini adalah 136 siswa kelas IV Sekolah Dasar. Instrumen yang digunakan adalah angket. Teknik analisis data menggunakan analisis regresi. Hasil penelitian menunjukkan bahwa peranan dalam keterlibatan orang tua terhadap motivasi siswa mencapi 39,7%. Dapat disimpulkan bahwa keterlibaatan orang tua memiliki pengaruh positif terhadap motivasi belajar siswa. Penelitian ini menujukkan pentingnya peran orang tua pada motivasi belajar siswa. Hasil penelitian ini diharapkan bisa memberi pemahaman pada pihak sekolah agar mengingatkan para orang tua siswa bahwa dukungan mereka sangat penting dalam proses pembelajaran. Oleh karena itu, semua pihak harus terlibat dalam meningkatkan kualitas pendidikan anak-anak.